Interleukin-17 producing cells in swine induced by microbiota during the early postnatal period - a brief research report - Stepanova, Hana; Scheirichova, Marketa; Matiasovic, Jan; Hlavova, Karolina; Sinkora, Marek; Stepanova, Katerina; Faldyna, Martin (Frontiers in Immunology, 2023)
Interleukin-17A (IL-17) is a pro-inflammatory cytokine involved in the immune response to many pathogens playing also a role in certain chronic and autoimmune diseases. The presented study focused on the early postnatal development of IL-17 producing cells in swine. In agreement with previous studies, αβ T-helper (CD3 + CD4 + ) and γδ T (CD3 + TCRγδ + ) cells were found to be the major producers of IL-17. In newborn conventional piglets, αβ T-helper cells positive for IL-17 were almost undetectable, but their frequency increased markedly with age in all issues examined, i.e., blood, spleen, and mesenteric lymph nodes (MLN). Additional analyses of CD8 and CD27 expression showed that the main αβ T-helper producers of IL-17 has CD8 + CD27 -phenotype in all tissues. IL-17 positive CD8 + CD27 + αβ T-helper subpopulation was found only in blood and spleen. The production of IL17 in CD8 -CD27 + αβ T-helper cells was always minor. In contrast, γδ T cells positive for IL-17 did not show a similar age-dependent increase in blood and spleen, whereas they increased in MLN. Because of the age-dependent increase in conventional animals, we included a comparison with germ-free piglets to show that the increase in IL-17 positive cells was clearly depended on the presence of the microbiota as the production in germ-free animals was negligible without any age-dependent increase.